Utilização do active shape model para análise de imagens médicas: localização do pulmão de crianças em radiografias para auxiliar no diagnóstico de pneumonia - Freire Sobrinho, Paulo (2017)
Contextualization: Technologies like CAD systems, become ideal as a second opinion, that is, to work in partnership with the doctor. For example, PneumoCAD can be used to perform a diagnosis of absence or absence of pneumonia in children 1 to <5 years of age using X-ray radiographs. Problems: However, the use of PneumoCAD requires a region of interest, referring to the lungs, manually. Based on difficulty and difficulty, we sought a solution that was not found in any research, applied to radiographs, involving PneumoCAD, through the active model, having as a patient children between the ages of 1 and <5 years. Proposal: It is then proposed the use of the active model, associated with the technique developed and called nsAlterar in improvement to segmentation based on ns . Materials and Methods: Fifty-six “padrão ouro” radiographs were submitted to MATLAB, in 8 steps, through modified and improved algorithms, as well as implemented support tools, such as: As well as measures of similarity to investigate quantitatively , On an efficiency of all resources employed for the same purpose. Results: With this question, we obtained, after an analysis of the experiments, a taxon of hits for the right of spraying 75.61% and for the left one in 63.41%, in which nsAlterar promoted the improvement in the distributions, even if They were not segmented correctly, through approximations properly. Conclusions: Based on the active model associated with nsAlterar and other resources, it was possible to complement a functionality of the PneumoCAD system, through the use of segmentation in reais, thus contributing to a higher efficiency and better results.